An IDM-Based Approach for Information Requirement in Prefabricated Construction. (27th January 2020) - Xu, Zhao; Abualdenien, Jimmy; Liu, Hao; Kang, Rui
Abstract : Prefabricated construction promotes providing better productivity and project results. Building models, including their elements' fabrication details, are complex structures that need accurate information delivery among the project participants and their partial designs. This paper extends the IFC data model to support prefabricated construction. Also, it discusses the advantages of systematically managing exchange requirements in a database to facilitate generating IDM (Information Delivery Manual). The paper first introduces a BIM-based collaborative work mode by sharing and extracting the model views. The core of the sharing is the establishment of view exchange standard about the linked model and the definition of exchange requirements based on the design process, leading to the formulation of the IDM standard again from the perspective of the actual design. Process maps covering architecture, structure, plumbing, mechanical engineering, and electrical engineering are made to show how to realize BIM-based collaborative work. Then the exchange requirements referred to the object and attribute of the BIM model which should be delivered in a special phase are defined in particular tables. To facilitate the automation of managing and exchanging requirements, a database management system is designed with its corresponding user-interface, which enhances the collaboration and delivery throughout the project life cycle. The proposed approach supports better information reuse and delivery among the project participants.